ANÁLISE DE PLANOS MUNICIPAIS DE GESTÃO INTEGRADA DE RESÍDUOS SÓLIDOS URBANOS EM MUNICÍPIOS DE PEQUENO E MÉDIO PORTE DO PARANÁ - CROVADOR, CLEYTON CRISTIANO (2022)
Twelve years after the enactment of the National Policy on Solid Waste (Política Nacional de Resíduos Sólidos - PNRS), the proper management of municipal solid waste (MSW) still presents itself as a challenge to Brazilian municipalities, and one of the requirements of this policy is the preparation, implementation and monitoring of the Municipal Plan for Integrated Management of Solid Waste (Planos Municipais de Gestão Integrada de Resíduos Sólidos - PMGIRS). Considering that this document is an important instrument for the adequacy of municipalities for waste management, the present study aimed to evaluate the PMGIRS of small and medium-sized municipalities in the state of Paraná, according to the minimum content established by the PNRS. The methodology used was configured in two stages, initially by documentary research, with the survey of the municipalities of the state and subsequent search on the Internet for the documents to be evaluated. In the second stage, the evaluation of the selected documents occurred, using an instrument for the survey of indicators. The first stage of the research indicated that of the 399 municipalities of Paraná, 204 of them informed that they have their PMGIRS finalized, and of these, 79 made the document available online, being randomly selected 11 small-sized and 14 medium sized municipalities. In the second stage, the evaluation resulted in the fulfillment of the minimum content between 5 and 13 indicators in the small-sized municipalities. For the medium-sized municipalities, compliance varied between 5 and 15 indicators. The indicator that was least met by the municipalities was related to "Disclosure of the PMGIRS", not being presented in any municipality, on the other hand, the indicator that had the highest compliance was about the "Procedure for waste management", being met in 100% of the municipalities evaluated. Categorizing the PMGIRS according to who was responsible for their elaboration, 15 municipalities were identified in which the municipality was responsible and 10 municipalities that hired an outsourced company. Still, the PMGIRS were elaborated between 2010 and 2019, with most of them dating from 2014 and 2017. Despite the fact that the municipalities do not present good PMGIRS and that the vast majority of municipalities do not have or do not disclose their documents online, this study presents an important finding of how the management scenario of RS in the state of Paraná is, fills in some gaps and offers, especially, subsidies that can be used for adjustments of PMGIRS in order to enable the implementation of actions that promote the search for a more sustainable development in the management of RSU from the interaction of institutional, social, economic and environmental dimensions.